GE_GERICHTE P/16271/2016 vom 15. Juli 2019 - GE Cour de justice (2019)
ACTE D'ORDRE SEXUEL AVEC UN ENFANT ; CONTRAINTE SEXUELLE ; DIRECTIVE(INJONCTION) ; TORT MORAL ; EXEMPTION DE PEINE | CP.187; CP.189; CP.44.al2; CP.52; CO.49